Improved cardiac magnetic resonance thermometry and dosimetry for monitoring lesion formation during catheter ablation. Issue 2 (21st February 2016) - Ozenne, Valéry; Toupin, Solenn; Bour, Pierre; de Senneville, Baudouin Denis; Lepetit‐Coiffé, Matthieu; Boissenin, Manuel; Benois‐Pineau, Jenny; Hansen, Michael S.; Inati, Souheil J.; Govari, Assaf; Jaïs, Pierre; Quesson, Bruno
Abstract : Purpose: A new real‐time MR‐thermometry pipeline was developed to measure multiple temperature images per heartbeat with 1.6×1.6×3 mm 3 spatial resolution. The method was evaluated on 10 healthy volunteers and during radiofrequency ablation (RFA) in sheep. Methods: Multislice, electrocardiogram‐triggered, echo‐planar imaging was combined with parallel imaging, under free breathing conditions. In‐plane respiratory motion was corrected on magnitude images by an optical flow algorithm. Motion‐related susceptibility artifacts were compensated on phase images by an algorithm based on Principal Component Analysis. Correction of phase drift and temporal filter were included in the pipeline implemented in the Gadgetron framework. Contact electrograms were recorded simultaneously with MR thermometry by an MR‐compatible ablation catheter. Results: The temporal standard deviation of temperature in the left ventricle remained below 2 °C on each volunteer. In sheep, focal heated regions near the catheter tip were observed on temperature images (maximal temperature increase of 38 °C) during RFA, with contact electrograms of acceptable quality. Thermal lesion dimensions at gross pathology were in agreement with those observed on thermal dose images. Conclusion: This fully automated MR thermometry pipeline (five images/heartbeat) provides direct assessment of lesion formation in the heart during catheter‐based RFA, which may improve treatment of cardiac arrhythmia by ablation. Magn Reson Med 77:673–683, 2017. © 2016 International Society for Magnetic Resonance in Medicine